2012
DOI: 10.1097/rlu.0b013e318252d2ed
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Diagnosis of Orbital Cavernous Hemangioma

Abstract: 99mTc-RBC imaging is safe, easy to perform, and highly accurate in providing adequate clinical and surgical management. As a noninvasive and highly specific method for diagnosing orbital hemangioma, 99mTc-RBC scintigraphy can avoid more invasive imaging or biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
3
5
0
3
Order By: Relevance
“…Nuclear scintigraphy with 99mTc‐RBC single photon emission CT is a noninvasive and highly specific method for diagnosing orbital hemangioma and showed 100% sensitivity and 88.9% specificity for the diagnosis of orbital cavernous hemangioma, with a positive predictive value of 90.9% and a negative predictive value of 100% in the recent literature …”
Section: Discussionmentioning
confidence: 97%
“…Nuclear scintigraphy with 99mTc‐RBC single photon emission CT is a noninvasive and highly specific method for diagnosing orbital hemangioma and showed 100% sensitivity and 88.9% specificity for the diagnosis of orbital cavernous hemangioma, with a positive predictive value of 90.9% and a negative predictive value of 100% in the recent literature …”
Section: Discussionmentioning
confidence: 97%
“…6,7 This imaging modality has also been shown to be highly accurate in the diagnosis of extracranial venous malformations. 8 Because the patient in this case had been completely asymptomatic, no treatment was offered. In symptomatic venous malformations in the head and neck, there are several treatment options that include a multidisciplinary approach based on lesion size and extent, such as laser therapy, embolization, percutaneous sclerotherapy, or surgical resection.…”
Section: Discussionmentioning
confidence: 97%
“…After a certain period of time, the tumour was filled with 99m Tc-RBC homogeneously. The technique of 99m Tc-RBC scintigraphy may also be used in the noninvasive evaluation of extrahepatic vascular lesions such as vascular tumours of the orbit, which show the characteristic scintigraphic pattern, and can be diagnosed as cavernous hemangioma with a high degree of certainty 8 . Sayit et al 9 reported that, in all patients with OCH whom they studied, the preoperative diagnosis was confirmed by the typical pattern of perfusion blood pool mismatch on the 99m Tc-RBC scintigraphy.…”
Section: Discussionmentioning
confidence: 99%